POTENSI LIMBAH PERTANIAN TANAMAN PANGAN SEBAGAI PAKAN TERNAK ROMINASIA DI KECAMATAN WAELATAKABUPATEN BURU - Dominggus de Lima; Ch. W. Patty (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2021)
Livestock is an important component to fulfil food need and as source of protein for the community which increase annually. These research objective was to determine the type of agricultural food crop waste, how much production of dry matter, crude protein, and Total Gigability Nutrit and also to find out how much the capacity of agricultural food crop waste in the Waelata District, Buru Regency. Feedstuff development is directed to optimize the use of local feed source, in particular crops waste. The results showed that crops waste available in Waelata were dominated respectively by rice (Oryza sativa L.) 92.17 %, sweet potato (Ipomoae batatas) 2.81 %, corn (zea mays ssp.) 1.89 %, peanut (Arachis hypogaea L.) 1.89 %, and cassava (manihot esculenta crantz) 1.12 %. Total dry matter production of the crops waste were rice (Oryza sativa L.) 2.52 tones/ha, sweet potato (Ipomoae batatas) 1.78 tone/ha, corn (zea mays ssp.) 0.63 tone/ha, peanut (Arachis hypogaea L.) 1.67 tones/ha, and cassava (manihot esculenta crantz) 0.41 tones/ha. Capacity of crops waste to support livestock systems based on dry matter, crude protein, Total Digestible Nutrient was respectivelly e.317 UT, 263 UT, and 3.134 UT.